Biomass and productivity responses of zooplankton communities to experimental thermocline deepening. (9th January 2014) - Sastri, Akash R.; Gauthier, Joanna; Juneau, Philippe; Beisner, Beatrix E.
Abstract : Lake thermocline depth is likely to be altered with climate change. We assessed the response of crustacean zooplankton biomass and productivity to an experimental whole‐lake manipulation of thermocline depth. Weekly sampling occurred in Experimental and Reference years and responses were assessed with a before—after‐control—impact design. While one of three lake basins remained un‐manipulated (control), two others experienced thermocline deepening via: active mixing simulating increased wind‐stress ('mixing with thermocline deepening'); and increased overall heat content, simulating greater water clarity ('thermocline deepening'). Thus, we simultaneously identified seasonal responses to three treatments: mixing with thermocline deepening, thermocline deepening alone, and an isolated mixing effect . Total crustacean zooplankton biomass was enhanced by all treatment effects, owing to positive responses to thermocline deepening in Bosmina and Daphnia and a positive cyclopoid copepod response to mixing. Enhancement of biomass production rates (BP) occurred only with thermocline deepening, with no effect of mixing alone. The lack of BP response to active mixing was likely due to compositional shifts from fast growing Daphnia to slower growing cylopoids. BP variation was explained by positive and negative relationships with mean water‐column temperature and hypolimnetic temperature, respectively. Hypolimnetic warming, occurring naturally with the seasonal thermocline descent was more dramatic for the active mixing manipulation. This loss of hypolimnetic refuge for Daphnia appears to have had a negative effect on the community daily production to biomass ratio (P : Bdaily ). Our study indicates a greater likelihood for reduced food‐web transfer efficiency under scenarios when mixing and hypolimnetic warming accompany thermocline deepening.